Search considered integral. - Barrows, Ryan (New York ACM, 2006)
A combination of tagging, categorization, and navigation can help end-users leverage the power of enterprise search.
Keywords: Information Systems; Information storage and retrieval; Information search and retrieval; Search process; Content analysis and indexing; Indexing methods; Computing Milieux; Management of Computing and Information Systems; Project and people management; Systems analysis and design; Design